A morphological view of the relationship between indirect flight muscle maturation and the flying needs of two species of advanced eusocial bees - Fernandez-Winckler, Fernanda [UNESP]; da Cruz-Landim, Carminda [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
This paper describes the flight muscles changes in relation to the age/function of the adult members of the colonies of two advanced species of eusocial bees: Apis mellifera (Apini) and Scaptotrigona postica (Meliponini). Here, are reported the results obtained through transmission electron microscopy studies, first describing a general overview of the flight muscle ultrastructure and second reporting on the ultrastructural changes that occur along the life stages/functions of workers, queens and males. The workers emerge with immature flight muscles, and the maturation takes about 20 days. In contrast, queens and males emerged with more advanced muscle differentiation, similar to workers after the 20 days of maturation. In both forager workers and laying queens, flight muscles showed signs of senescence, but not in sexually mature males. The differences among life phases, individual classes and species are discussed in relation to their functions in the colony. (C) 2008 Published by Elsevier Ltd.
Keywords: Flight muscles; Honeybee; Stingless bee; Castes; Male; Ultrastructure; Social functions